Thymoquinone Potentiates the Effect of Phenytoin against Electroshock-Induced Convulsions in Rats by Reducing the Hyperactivation of m-TOR Pathway and Neuroinflammation: Evidence from In Vivo, In Vitro and Computational Studies - Faheem Hyder Pottoo; Mohammed Salahuddin; Firdos Alam Khan; Fadhel Alomar; Marwa Abdullah AL Dhamen; Abrar Fouad Alhashim; Hawra Hussain Alqattan; Mohamed S. Gomaa; Mohammad N. Alomary (Pharmaceuticals, 2021)
Epilepsy is a chronic neurodegenerative disease characterized by multiple seizures, hereto 35% of patients remain poor responders. Phenytoin (PHT; 20 and 40 mg/kg) and thymoquinone (THQ; 40 and 80 mg/kg) were given alone and as a low dose combination for 14 days (p.o), prior to challenge with maximal electroshock (MES; 180 mA, 220 V, 0.2 s). Apart from observing convulsions, hippocampal mTOR, IL-1β, IL-6 and TNF-α levels were measured. Hippocampal histomorphological analysis was also conducted. In vitro cell line studies and molecular docking studies were run in parallel. The results revealed the synergistic potential of the novel duo-drug combination regimen: PHT (20 mg/kg) and THQ (40 mg/kg) against MES-induced convulsions. MES amplified signaling through mTOR, and inflated the levels of proinflammatory markers (IL-1β, IL-6 and TNF-α), which was significantly averted (p < 0.001) with the said drug combination. The computational studies revealed that PHT and THQ cooperatively bind the active site on Akt (upstream target of m-TOR) and establish a good network of intermolecular interactions, which indicates the sequential inhibition of PI3K/Akt/m-TOR signaling with the combination. The combination also increased cell viability by 242.81% compared to 85.66% viability from the the toxic control. The results suggest that the PHT and THQ in combination possesses excellent anticonvulsant and neuroprotective effects.